Do Reserve Portfolios Respond to Exchange Rate Changes Using a Portfolio Rebalancing Strategy? : An Econometric Study Using COFER Data - Lim, Ewe-Ghee (IMF Working Papers; Working Paper ;, 2007)
This paper tests whether reserve portfolios respond to exchange rate changes with a portfolio rebalancing strategy, which requires the purchase of depreciating currencies and sale of appreciating ones. The paper finds empirical support for the strategy, in particular that dollar depreciation/appreciation results in rebalancing switches vis-a-vis the other major reserve currency, the euro; valuation changes in the minor currencies tend to result in switches among themselves. The finding implies that currency diversifications in response to exchange rate changes have thus far tended to be stabilizing for exchange markets; it also helps explain the relative stability of reserve currency shares.